Comparing the Effectiveness of Cognitive-Behavioral Couple Therapy and Gottman Couple Therapy on Marital Satisfaction and Problem Solving Styles in Couples Referring to Counseling Centers in Lamard and Mohr City - S. Abdulmajid Mosavi; Parvin Ehteshamzadeh; Behnam Makvandi; Reza Pasha; Saeed Bakhtiaripoor (Iranian Evolutionary Educational Psychology Journal, 2023)
Objective: The present study aimed to compare the effectiveness of cognitive behavioral couple therapy and Gottman couple therapy on marital satisfaction and problem solving styles of couples. Methods: The statistical population is all the referrals to the counseling and psychological services center in Mohr and Lamard cities in Fars province, Iran. Participants were 45 people that randomly selected and randomly assigned to cognitive-behavioral couple therapy group (15 people), Gottman couple therapy group (15 people) and control group (15 people). The ENRICH Marital Satisfaction (EMS) Scale was used to measure marital satisfaction and Cassidy and Long (1996) Problem-solving style questionnaire was used to measure problem solving styles. In order to analyze data, the mean and standard deviation were calculated in the descriptive statistics part and multivariate covariance analysis method was used in the inferential statistics part. Results: According to the results, cognitive behavioral couple therapy had a significant effect on marital satisfaction and problem solving styles. Also, results indicated that Gottman couple therapy had a significant effect on marital satisfaction and problem solving styles. Conclusions: According to the results there is a significant difference between two interventions in problem solving styles but there is no significant difference between two approaches.